Heritage and identity: The vernacular transformation of De Tjolomadoe - Widiantara, I Wayan Andhika; Pratama, Rama N.; Kamal, Astia (The Journal of City: Branding and Authenticity, 2024)
Background: This research paper focuses on the adaptive reuse of the De Tjolomadoe (Colomadu) heritage sugar factory within the field of vernacular architecture. Methods: Utilizing qualitative research methods such as in-depth interviews, site observations, and archival analysis, it examines the preservation of industrial heritage through its integration into vernacular architectural practices, yielding insights for sustainable development. Findings: The De Tjolomadoe factory, a prominent Indonesian historical and cultural landmark, serves as a compelling case study in adaptive reuse, offering significant findings. Firstly, it illustrates how adaptive reuse effectively preserves cultural identity by seamlessly blending vernacular design elements and traditional building techniques, thereby maintaining a strong connection to its historical and cultural heritage. Secondly, the De Tjolomadoe case exemplifies adaptive reuse as a sustainable development strategy. By utilizing local resources and adhering to vernacular construction methods, the project minimizes environmental impact while generating economic and social benefits for the community. Community engagement emerges as a crucial factor in the success of adaptive reuse projects, as actively involving local communities ensures the authenticity and relevance of such initiatives. Moreover, the transformation of the De Tjolomadoe factory into a cultural destination underscores its substantial economic impact on the region. Similar adaptive reuse projects have the potential to boost tourism, stimulate local economies, and preserve cultural heritage. Conclusion: The lessons drawn from the De Tjolomadoe case offer practical insights and principles guiding future adaptive reuse endeavours, emphasizing cultural preservation, sustainability, community participation, and economic viability. Novelty/Originality of this article: These findings contribute to the growing knowledge base on the adaptive reuse of industrial heritage sites within the context of vernacular architecture, inspiring and informing initiatives aimed at revitalizing our industrial heritage for future generations.